Behavior of metals in a combined wastewater collection system in Ostrava, Czech Republic - Raclavska, Helena; Drozdova, Jarmila; Skrobankova, Hana; Raclavsky, Konstantin (Water environment research, 2015)
In combined wastewater collection systems, the concentrations of metals and the form of metal occurrence (dissolved form and bonding of metals to total suspended solids) influence the efficiency of capturing metals into sludge in wastewater treatment plants. The variability of metal concentrations was determined for 12 sampling sites during dry weather periods (DWP) and wet weather periods (WWP). Wastewater during DWP contain in dissolved form 77% of cadmium, 75% of nickel, 66% of arsenic, 57% of manganese and 50% of zinc and copper. Other metals are preferably bound to suspended particulates: 65% of chromium, iron, vanadium, mercury and 91% of lead. Comparison of metal concentrations in wastewater during DWP and WWP can be used to determine non-point source contributions. During WWP, metal concentrations increase by 24 to 25% for cadmium and zinc, 22% for nickel and 18% for copper. Urine and feces are responsible for a very small portion (<15%) of the total content of metals. Households are the main source of cadmium and copper (64% of total concentrations of these metals in wastewater).
Keywords: Particle Size; Wastewater; Sewage; Cities; monitorování životního prostředí; Water Purification; Czech Republic; Environmental Monitoring; velikost částic; těžké kovy; čištění vody; odpadní vody; Waste Water; velkoměsta; odpadní voda; Česká republika; Metals, Heavy; Suspensions; suspenze